Mass transfer in bubble column contractors - Rudolph, Victor (Department of Chemical Engineering, 2016)
Gas holdup and overall volumetric mass transfer coefficients in bubble column contactors have been investigated for water and aqueous electrolyte solutions. Two methods were used to obtain experimental data on volumetric mass transfer coefficients: the steady state oxidation technique and a transient method. The former technique was found to be unsuitable for absorption measurements because chemical enhancement of mass transfer, due to simultaneous absorption and fast reaction, caused erroneously high mass transfer coefficients to be evaluated. In the transient experiments the effect of superficial gas velocity, concentration of electrolytes in solution, bubble column diameter and gas inlet orifice diameter on the gas holdup and the mass transfer rate, were investigated. The experimental data for gas holdup and overall mass transfer coefficients obtained both in this study and from the literature have been correlated by dimensionless equations.